Rhodium‐catalyzed Decarbonylation of Acylsilanes. Issue 12 (29th November 2022) - Yoshida, Tomoki; Kodama, Takuya; Tobisu, Mamoru
Abstract: The rhodium‐catalyzed decarbonylation of acylsilanes is reported. This reaction proceeds through the cleavage of a carbon–silicon bond in acylsilanes. When two different acylsilanes are reacted in one batch, crossover products are formed. These results indicate that two mechanisms are operating in this catalytic reaction. Abstract : A carbon –silicon bond in acylsilanes can be activated by a rhodium(I) catalyst. A rhodium‐catalyzed decarbonylation of acylsilane is developed for the formation of arylsilanes.